Analysis of Household Food Security of Beef Cattle Livestock in Jambenenggang Village - Yepi Sopian; Siti Munjiah; Sri Mulyani; Warda Mutiara; Wini Widanti Azijah Damara (Indonesian Journal of Society Development, 2023)
This community service was carried out at the Dasa Jambenenggang beef cattle farming MSME, Kebonpedes District, Sukabumi Regency. The activity was carried out to analyze the food security of beef cattle farming for micro and small business actors in Jambenenggang Village. Mastery of digital marketing media is still very minimal for micro-small business actors in this case, we can see from the many existing products but it is difficult to compete with other products in online buying and selling media. To realize food security for the people of Jabenenggang village, namely by analyzing the adequacy of food availability , quality of food security, Stability of food availability without fluctuation from season to season or from year to year, Constraints in carrying out food security for the community. This beef cattle farming business continues to use traditional methods, although marketing is not with digital media but Pak Idang's beef cattle farm this can cut 5 cows per day according to the order target and the selling price can go up because of the soaring number of orders